Well my man, if it does not give you a value for x.... your answer would be 2x
That answer is incorrect and it’s false
Answer:
the answer would be 2
Step-by-step explanation:
you'll get the answer by dividing
Answer:
16
Step-by-step explanation:
f ( x ) = 3x² - 2x
To find : f ( - 2 )
f ( - 2 ) = f ( x )
Here,
x = - 2
f ( - 2 ) = 3 ( - 2 )² - 2 ( - 2 )
= 3 ( 4 ) - 2*( - 2 )
= 3*4 + 4
= 12 + 4
f ( - 2 ) = 16
1) neither. that’s not one of your answer choices so just pick one (maybe odd ♀️)
2) 2 is the answer. Plug in 1 for x, raise everything to its power (which will end up being 1), then use PEMDAS to solve